PLEISTOCENE AND RECENT DEGLACIATION IN SVALBARD: IMPLICATIONS FOR TIDE-GAUGE, GPS AND VLBI MEASUREMENTS - Hagedoorn J.M.; Wolf D. (My University, 2003)
Apart from sea-level change caused by ocean-water volume change, tide-gauge measurements are also affected by vertical movement of the earth's surface and by geoid change. To study these phenomena more closely, we consider the tide-gauge station at Ny-Ålesund, Svalbard, where vertical movements are controlled by GPS and VLBI measurements. Whereas the tide-gauge record indicates a relative sea-level fall of about 2.6 mm a−1, the GPS and VLBI measurements suggest a land uplift of about 5.6 mm a−1. We predict the deglaciation-induced vertical movement and geoid change by combining the Pleistocene ice model ICE-3G with the newly developed Recent ice model SVAL. We find that, for particular deglaciation histories and earth models with an asthenosphere, the predicted land uplift matches the measured land uplift rather closely. However, for these combinations of ice and earth models, the predicted sea-level fall is consistently too large by at least 3 mm a−1. Considering the uncertainties and simplifications involved in the study, the discrepancy weakly suggests a sea-level rise due to increased ocean-water volume.
Keywords: Pleistocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен